2021
DOI: 10.1111/jeb.13897
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of sex‐specific heat stress tolerance and larval Hsp70 expression in populations of Drosophila melanogaster adapted to larval crowding

Abstract: The ability to tolerate temperature stress is an important component of adult fitness. In holometabolous insects like Drosophila melanogaster, adult stress resistance can be affected by growth conditions experienced during the larval stages. Although evolution under crowded larval conditions is known to lead to the correlated evolution of many adult traits, its consequences on adult heat stress tolerance have not been investigated. Therefore, in the present study, we assessed the adult heat stress tolerance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
(100 reference statements)
0
9
0
Order By: Relevance
“… 7 , 16 , 17 , 18 , 19 Studies in Drosophila melanogaster have been invaluable in uncovering the plastic responses to larval crowding. For instance, larvae developing in crowded conditions have upregulated expression of heat-shock proteins in response to the stress of the developmental environment, 20 , 21 , 22 which may be involved in a hormesis-like response that leads to increased lifespan and fitness benefits in broader ecological contexts. 21 , 23 , 24 , 25 …”
Section: Introductionmentioning
confidence: 99%
“… 7 , 16 , 17 , 18 , 19 Studies in Drosophila melanogaster have been invaluable in uncovering the plastic responses to larval crowding. For instance, larvae developing in crowded conditions have upregulated expression of heat-shock proteins in response to the stress of the developmental environment, 20 , 21 , 22 which may be involved in a hormesis-like response that leads to increased lifespan and fitness benefits in broader ecological contexts. 21 , 23 , 24 , 25 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other fitness related traits, especially those related to reproduction such as courtship frequency, mating and reproduction (Shenoi, Banerjee, et al, 2016) have been shown to be in favour of crowded males, or not different. Further, crowded males do better than control males (under crowding) in other life‐history traits such as immune response (Kapila, Kashyap, Poddar, et al, 2021), heat‐shock response (Kapila, Kashyap, Gulati, et al, 2021) and longevity (Shenoi, Ali, & Prasad, 2016). While we cannot completely rule out the possibility that body size influences mating and reproductive success in our experiment, the small difference in size and evolution in other life‐history traits point to the evolution of mating and reproductive success, rather than a by‐product of differing body sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Since larval crowding scenarios are common in nature and are known to affect adult traits (Bierbaum et al, 1989; Kapila, Kashyap, Gulati, et al, 2021; Kapila, Kashyap, Poddar, et al, 2021; Roper et al, 1996; Shenoi, Banerjee, et al, 2016), the effect of larval crowding and evolution under crowded larval environments on sexual selection is an important avenue of research. Crowding is especially important in holometabolous insects such as Drosophila , where adults lay eggs in ephemeral habitats and juveniles are largely restricted to compete at the egg‐laying sites (Atkinson, 1979).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the adaptation to larval crowding by Hsp-70 expression improved the heat-stress tolerance of D. melanogaster. The studies provided insight on how pre-adult conditions influence the heat stress response and affect adult fitness [14]. The two examples of important model organism-abiotic perturbation helped to understand the adaptation to heat stressed environments at different phenotypic levels, like organismal growth and lifespan.…”
Section: Model Organisms In Perturbation Researchmentioning
confidence: 99%